Jack - Homes, A. M. (New York Vintage Books, 1990)
Fifteen-year-old Jack's confused feelings for his father, who left him and his mother four years earlier, are further complicated when he finds that his father is gay.
Keywords: Fathers and sons -- Fiction; Gay fathers -- Fiction; Homosexuality -- Fiction